Intensity and frequency of moral distress in Brazilian nurses - Flavia Regina Souza Ramos; Priscila Orlandi Barth; Laura Cavalcanti de Farias Brehmer; Graziele de Lima Dalmolin; Mara Ambrosina Vargas; Dulcinéia Ghizoni Schneider (SciELO, 2020)
Abstract Objective: To evaluate the frequency and intensity of moral distress in Brazilian nurses. Method: Cross-sectional study performed with nurses from 27 Brazilian states through application of the Brazilian Moral Distress Scale in Nurses (Portuguese acronym: EDME-Br) and descriptive statistical analysis. Results: Participation of 1,226 Brazilian nurses in the study. The intensity and frequency of overall moral distress were rated as moderate level, with averages of 3.08 (± 1.45) and 2.94 (± 1.37), respectively. Specifically, the highest intensity and frequency was related to the factors Acknowledgement, power and professional identity and Work teams, while the lowest was related to the factor Defense of values and rights. Conclusion: Moral distress occurs in precarious work environments, with little expressiveness of the nurses' role. One highlights the importance of the problem in terms of its amplitude and multicausality, reaching professionals acting in different work contexts.